Where on Earth are the “tropics”? - Kenneth J. Feeley; James T. Stroud (Frontiers of Biogeography)
The tropics have long been a focal point of interest in ecology and evolutionary biology - but where actually are the tropics? Classically, the tropics have been defined as all areas lying between 23.4° North and South as these zones receive direct overhead solar radiation at some point during the year. However, a suite of different environmental and climatic characteristics have also been employed to classify regions as tropical or not. The aims of this paper are to 1) briefly review some of the different criteria commonly used to define the tropics, 2) map the extent and distribution of tropical land areas according to these different criteria, and 3) asses the concordance between these criteria and a sample of recent “tropical” studies. More specifically, we review eight criteria that are frequently used (implicitly or explicitly) to define the tropics. We then map the location and extent of land areas that are “definitely tropical” (i.e., the core tropics) and areas that are “tropical by most definitions”. Finally, we examine how the different classifications apply to tropical research through an analysis of the study locations of >200 recent tropical biology articles. Depending on the definition, the extent of the terrestrial tropics ranges from 23 million to 66 million km2 – a nearly threefold difference. Likewise, the classification of many areas as being tropical vs. non-tropical depends on the specific criterion employed. Of the tropical studies reviewed here, only 44% were based on data collected from the core tropics, and 12% of tropical studies were based on data collected from sites outside of the geographic tropics but with tropical climates. Many different criteria are used to classify areas as tropical vs. non-tropical, leading to inconsistencies when estimating the extent of tropical areas and variation in the classification of ecosystems and species as being tropical vs. non-tropical.